P105 MIRNA483-3P AND MIRNA221 DYSREGULATION AND CORRELATION WITH SURVIVAL IN ESOPHAGEAL ADENOCARCINOMA (EAC). (23rd November 2019) - Isidori, F; Bozzarelli, I; Lugaresi, M; Malvi, D; Mastracci, L; Hoefnagel, S J M; Räsänen, J; Söderström, H; Raulli, G; D'Errico, A; Fiocca, R; Seri, M; et al.
Abstract: Aim: Our study aimed to characterize miR-221 and 483-3p dysregulation and to correlate their expression with clinical outcomes in patients submitted in first instance to surgical therapy (naïve patients) for esophageal adenocarcinoma (EAC). Background & Methods: MicroRNA (miRNAs) are small, noncoding RNAs that play important roles in several biological processes by fine-tuning gene expression1. In a cohort of well-characterized EAC, we analyzed the expression of miRNAs. RNA was extracted from formalin-embedded (FFPE) surgical specimens of normal gastric tissues and EACs, classified according to BIM/GIM classification (BIM=Barrett's intestinal metaplasia, GIM=Gastric intestinal metaplasia): 43 BIM-/GIM-, 32 BIM+/GIM-, 2 BIM+/GIM+, 9 BIM-/GIM+). Expression of 754 human miRNAs was profiled in 8 cases with TaqMan MicroRNA Array card A1.1/B3.0. miR-221 and 483-3p validation was performed with single TaqMan probes on all 85 FFPE samples. miR-221 and miR-483-3p were also analyzed in a cohort of 39 fresh-frozen biopsies (29 EAC and 10 normal esophageal tissues). In 3 EAC cell-lines (OE-19, OE-33, FLO-1)2 we tested the expression of miR-221 and miR-483-3p3 and of two major targets ( PTEN and SMAD4, respectively). Correlations between miRNAs and clinical outcomes were calculated using Kruskal-Wallis, Mann-Whitney, t-Student's and Kaplan-Meier tests. Results: miR-221 and 483-3p resulted upregulated from the MicroRNA Array card analysis. This increase was confirmed in two independent cohorts (FFPE-cohort: miR-483-3p p=0.0065; fresh-frozen-cohort: miR-483-3p p<0.0001, miR-221 p=0.0062). Statistical analysis showed an upregulation of both miRNAs, in particular miR-483-3p (p<0.0001), in BIM-/GIM-, compared to BIM+/GIM-. miR-221 and 483-3p up- regulation correlated with reduced cancer-specific survival in FFPE samples (miR-483-3p p=0.053, miR-221 p=0.001). We demonstrated a significantly increase for miR-483-3p (p=0.01) with a trend toward reduction of SMAD4 expression in FLO-1 compared to other cell-lines. Conclusions: We identified an up-regulation of miR-221 and miR-483-3p, which might contribute to cancer progression. In the most aggressive cell line, FLO-1, we observed an increased expression of miR-483-3p, with SMAD4 reduction. Further studies are warranted to elucidate in depth the role of miR-221 and miR- 483-3p in EAC.